Data and Applications Security and Privacy XXXVII 37th Annual IFIP WG 11.3 Conference, DBSec 2023, Sophia-Antipolis, France, July 19-21, 2023, Proceedings - Atluri, Vijayalakshmi; Ferrara, Anna Lisa. (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This volume LNCS 13942 constitutes the refereed proceedings of the 37th Annual IFIP WG 11.3 Conference, DBSec 2023, in Sophia-Antipolis, France, July 19-21, 2023. The 19 full papers presented together with 5 short papers were carefully reviewed and selected from 56 submissions. The conference focuses on secure data sharing; access control and vulnerability assessment; machine learning; and mobile applications.
Privacy 1 -- (Local) Differential Privacy has NO Disparate Impact on Fairness -- Building Quadtrees for Spatial Data under Local Differential Privacy -- Privacy-Preserving Genomic Statistical Analysis under Local Differential Privacy -- Secure Data Sharing -- New Results on Distributed Secret Sharing Protocols -- Probabilistic Fingerprinting Scheme for Correlated Data -- Optimized stream-cipher-based transciphering by means of functional-bootstrapping -- Applications 1 -- Control is Nothing Without Trust: A First Look into Digital Identity Wallet Trends -- Impact of using a privacy model on smart buildings data for CO2 prediction -- Digital Twins for IoT Security Management -- Privacy 2 -- Distribution Invariant Local Differential Privacy For Federated Learning -- On the utility gain of iterative bayesian update for locally differentially private protocols -- Differentially Private Streaming Data Release under Temporal Correlations via Post-processing -- Access Control and Vulnerability Assessment -- Assurance, Consent and Access Control for Privacy-Aware OIDC Deployments -- Maintain High-Quality Access Control Policies: An Academic and Practice-Driven Approach -- SMET: Semantic Mapping of CVE to ATT&CK and its Application to Cybersecurity -- Machine Learning -- Classification Auto-Encoder based Detector against Diverse Data Poisoning Attacks -- CodeGraphSMOTE - Data Augmentation for Vulnerability Discovery -- An Autoencoder-Based Image Anonymization Scheme for Privacy Enhanced Deep Learning -- Mobile Applications -- Security and Privacy of Digital Mental Health: An Analysis of Web Services and Mobile Applications -- Android Code Vulnerabilities Early Detection using AI-powered ACVED Plugin -- A Dynamic Approach to Defuse Logic Bombs in Android Applications -- Applications 2 -- AMOE: a Tool to Automatically Extract and Assess Organizational Evidence for Continuous Cloud Audit -- Essential Information from Vulnerability Descriptions for CVSS Evaluation -- Hybrid Consensus in Blockchain Protocols for correctness and Progress.
Keywords: Data protection; Computers; Artificial intelligence; Data structures (Computer science).; Information theory; Database management; Application software; Data and Information Security; Computing Milieux; Artificial Intelligence; Data Structures and Information Theory; Database Management System; Computer and Information Systems Applications